Relationship between Untreated Dental Caries and Weight and Height of 6- to 12-Year-Old Primary School Children in Bangladesh - Masuma Pervin Mishu; Martin Hobdell; Mahfujul Haq Khan; Richard M. Hubbard; Wael Sabbah (Hindawi Limited, 2013)
Background. Children in low-income developing countries are likely to suffer from undergrowth. Dental caries is another common problem in these countries. Aim. To examine the association between untreated dental caries in primary and permanent teeth with age-adjusted height and weight among 6-12-year-old children in Bangladesh. Design. Social, behavioural, and clinical data were collected from 1699 children in nine different randomly selected primary schools in socially deprived areas of Bangladesh. The associations of age-adjusted weight and height and being underweight with dental caries were examined adjusting for sex, area of residence, socioeconomic position, skipping meals, tooth cleaning, and doctor visits. Results. 26% of the children were underweight and 55% had untreated dental caries. Children with at least one decayed tooth were significantly underweight with odds ratios 1.6 (95% CI 1.1, 2.3) and 1.5 (95% CI 1.1, 2.0) for 6-8-years and 9-12-year-old children, respectively, in the adjusted model. The number of decayed teeth was inversely and significantly associated with the standardized age-adjusted weight. Conclusions. The findings highlight the association between untreated dental caries and being underweight in primary school children in socially deprived areas in low-income developing countries and emphasize the need to integrate oral and general health policies with social policies.